Purtscher-like Retinopathy Associated with Systemic Lupus Erythematosus. (2nd January 2016) - Kunavisarut, Paradee; Pathanapitoon, Kessara; Rothova, Aniki
Abstract: Purpose : To report on clinical manifestations of Purtscher-like retinopathy (PLR) associated with systemic lupus erythematosus (SLE) and visual outcomes. Methods : We performed a retrospective cohort study of 11 patients (21 affected eyes) with PLR in SLE. Results : All patients were treated with systemic corticosteroids ± immunosuppressive agents. Ocular therapy included intravitreal injections with bevacizumab in 18/21 eyes and posterior sub-Tenon injections with triamcinolone acetonide 13/21 eyes. Panretinal photocoagulation (PRP) was performed in 19/21 eyes and pars plana vitrectomy was required in 5/21 eyes. Visual improvement was found at follow-up of 3 and 6 months ( p = 0.05). Poor visual outcome was associated with presence of neovascularizations at onset ( p = 0.009), development of vitreous hemorrhage during PRP ( p = 0.015), and active status of SLE after onset of PLR ( p = 0.029). Conclusions : PLR might manifest as a devastating complication of SLE. We recommend treating any systemic activity of SLE and starting an early ocular treatment.